The Ahlmannryggen group, the viddalen formation and the associated igneous rocks in the viddalen area, western droning Maud land, Antarctica - Bredell, Johannes H. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 1976.